Reception of Darwinism in mid-to late Nineteenth-Century Nova Scotia - Reynolds, Andrew; MacNeil, Christie; Jabalee, Mitchell (Scientia Canadensis, 2020)
Reaction to Darwin’s theory of evolution within the natural history community of nineteenth-century Nova Scotia focused on his use of hypothesis to account for a diversity of facts about the origin of species. Critics here, as elsewhere, faulted Darwin’s reasoning for straying from proper Baconian inductive method. Those locally engaged in natural history were inclined to stick closely to a descriptive inventory of the colony’s (after 1867, the province’s) natural resources. More fundamentally, Darwin’s approach challenged the mission of natural theology to support a providential reading of the natural world and humanity’s place within it. A review of publications in the Proceedings and Transactions of the Nova Scotian Institute for Natural Science and a private-diary account of a discussion emerging from a Mechanics Institute lecture during the 1860s and ‘70s reveals how members reacted critically to Darwin’s science while insisting on the compatibility of science and religion.